Analyzing the Financial Dynamics of Tourism and Their Economic Impact in Nepal - Adhikari, Shiva Raj (The Gaze: Journal of Tourism and Hospitality, 2024)
Tourism is pivotal in Nepal’s economic development as it contributes to employment generation, foreign exchange earnings, and regional diversification. However, despite its growing importance, empirical studies examining the sector’s financial flows and economic returns remain limited. This study addresses that gap by adopting a mixed-methods approach, integrating quantitative analysis of macroeconomic indicators with qualitative insights from policy and stakeholder perspectives. Secondary data from 2015 to 2023 were collected from the Nepal Rastra Bank, the Ministry of Culture, Tourism and Civil Aviation, and international development agencies. Key indicators analyzed include tourism GDP contribution, employment elasticity, loan disbursements, private sector investment, and foreign direct investment. Tools such as trend analysis and correlation measurement were applied to assess tourism’s economic impact. The findings reveal that tourism contributes over 8% to national GDP and supports more than 1 million jobs, with notable effects in rural economies through ecotourism, homestays, and community-based enterprises. Public-private partnerships and targeted credit schemes significantly enhanced infrastructure and employment outcomes, while digital platforms and niche tourism spurred innovation and investment. Despite progress, challenges such as credit inaccessibility, regional disparities, and environmental externalities persist. Anchored in endogenous growth theory, the financial accelerator model, and institutional economics, this research recommends expanding financial inclusion, promoting rural investment, and integrating sustainability into tourism policy frameworks. The study supports evidence-based policymaking for a more equitable and resilient tourism sector in Nepal.